Does decentralization good for reducing communal conflict? A multilevel analysis of communal conflict at Indonesiaâ€™s villages 2008-2014 - Rusyiana, Aris; Sujarwoto, Sujarwoto (JPAS (Journal of Public Administration Studies), 2017)
Whether decentralization is good for reducing communal conflict is still debatable. This study examines the linkage between three types of decentralization and communal conflict in Indonesia. Data come from the Village National Census (Podes) 2008-2014 (N=234,717).Â  Results of multilevel logit regression shows that only administrative decentralization that significantly associated with reducing communal conflict, while fiscal and political decentralization are not. The findings suggest that decentralization work for reducing communal conflict through better capacity of local bureaucrats.